Sediment transport patterns and beach morphodynamics in the semi-enclosed bay of Platis Gialos, Sifnos Island, Aegean Sea - Petropoulos, A.; Evelpidou, N.; Kapsimalis, V.; Anagnostou, C.; Karkani, A. (Zeitschrift für Geomorphologie, 2022)
Pocket beaches are a large part of the Greek coastline, with strong touristic, economic and natural interest. Their morphological characteristics and wave forcing are the main factors influencing their evolution, while the most commonly observed dynamic is beach rotation due to prevailing wave direction. Human activities and climate change call for a better management for these areas, necessitating, therefore, the identification of coastal geomorphodynamic processes. This paper focuses on the geomorphological and sedimentological dynamic processes of Platis Gialos Bay (Sifnos), which have given rise to the present setting. Beach orientation, slope, length, geology, Posidonia Oceanica, degree of embayment, sedimentology and closure are some parameters that must be considered to calculate the morphodynamic and stability indicators that prevail at the beach. Wave exposure forcing conditions, longshore – rip current direction, are also hydrodynamic processes to be determined, as they play a significant role in sediment transport. A number of methodologies took place in order to determine the level of disturbance of this dynamic equilibrium, which included morphological mapping, sedimentary classification, shoreline displacement/evolution monitoring, hydrodynamic and sedimentary modelling. The exposure of the coast to the southern waves, the reduced sediment supply from the local fluvial network, human activities and the construction of the fishing shelter have led the area to a continuous erosion and coastline retreat in its western and central part, in contrast to the eastern part, where there is a continuous deposition reflected by coastal accretion and the formation of a shallow environment.